Extreme variation in recombination rate and genetic diversity along the Sylvioidea neo‐sex chromosome. Issue 13 (6th June 2022) - Ponnikas, Suvi; Sigeman, Hanna; Lundberg, Max; Hansson, Bengt
Abstract: Recombination strongly impacts sequence evolution by affecting the extent of linkage and the efficiency of selection. Here, we study recombination over the Z chromosome in great reed warblers ( Acrocephalus arundinaceus ) using pedigree‐based linkage mapping. This species has extended Z and W chromosomes ("neo‐sex chromosomes") formed by a fusion between a part of chromosome 4A and the ancestral sex chromosomes, which provides a unique opportunity to assess recombination and sequence evolution in sex‐linked regions of different ages. We assembled an 87.54 Mbp and 90.19 cM large Z with a small pseudoautosomal region (0.89 Mbp) at one end and the fused Chr4A‐part at the other end of the chromosome. A prominent feature in our data was an extreme variation in male recombination rate along Z with high values at both chromosome ends, but an apparent lack of recombination over a substantial central section, covering 78% of the chromosome. The nonrecombining region showed a drastic loss of genetic diversity and accumulation of repeats compared to the recombining parts. Thus, our data emphasize a key role of recombination in affecting local levels of polymorphism. Nonetheless, the evolutionary rate of genes (dN/dS) did not differ between high and low recombining regions, suggesting that the efficiency of selection on protein‐coding sequences can be maintained also at very low levels of recombination. Finally, the Chr4A‐derived part showed a similar recombination rate as the part of the ancestral Z that did recombine, but its sequence characteristics reflected both its previous autosomal, and current Z‐linked, recombination patterns.